2000
DOI: 10.1002/1097-0282(20001015)54:5<355::aid-bip60>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of β-casein hydrolysis by wild-type and engineered trypsin

Abstract: Apparent rate constants of tryptic hydrolysis of amide bonds containing Arg and Lys residues in β‐casein were determined by the analysis of kinetics of accumulation of 17 major peptide components revealed by high performance liquid chromatography. When studying pH influence on Arg/Lys bond cleavage preference, averaged rate constants over several ArgX and LysX bonds were used for analysis of kinetics of wild‐type trypsin, K188H, K188F, K188Y, K188W, and of K188D/D189K mutants. The pKa1 value of 6.5 was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
(38 reference statements)
0
32
0
Order By: Relevance
“…17 In the comparison with globular proteins, casein is known to be easily hydrolysed by proteases because of its elevated conformational flexibility and the abundance of the enzymeaccessible peptide bonds. 14 It was reported that clusters of hydrophobic amino acid residues in the polypeptide chain of casein substrate cause hydrophobic interaction to be responsible for the steric obstacles shielding peptide bonds against enzymatic attack. 3,14 For the proteolysis of β-CN, the fluorescence shift was also attributed to the increase of the water accessibility of Trp residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In the comparison with globular proteins, casein is known to be easily hydrolysed by proteases because of its elevated conformational flexibility and the abundance of the enzymeaccessible peptide bonds. 14 It was reported that clusters of hydrophobic amino acid residues in the polypeptide chain of casein substrate cause hydrophobic interaction to be responsible for the steric obstacles shielding peptide bonds against enzymatic attack. 3,14 For the proteolysis of β-CN, the fluorescence shift was also attributed to the increase of the water accessibility of Trp residue.…”
Section: Resultsmentioning
confidence: 99%
“…This effect known as masking of peptide bonds was pointed to be one of the main limiting factors of proteolysis. 3,14 Additionally, enzyme inhibition is a complex process, which includes interaction of the enzyme with the set of various proteolysis products. Consequently, simplifications are required for proteolysis models that can be used for quantitative estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Because the initial proteolytic reaction is focused on a single site, the kinetic analysis is practical and unambiguous. Computational modeling of proteolytic reactions indicates that even a minor secondary cleavage pathway can have a significant impact on the calculated equilibrium and rates (63,64). These concerns make it vital that measurements of dynamic motion based on the disappearance of starting material be the result of a single cleavage pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the pH (7e10) affects the charge state of the amino acids on the substrate (Lys, Arg). This also resulted in significant changes in the hydrolysis patterns (Vorob'ev et al, 2000). Different behaviour in the formation of peptides was also observed with optimum pH for the formation of some of the peptides.…”
Section: Determination Of the Selectivitymentioning
confidence: 91%
“…In this way, the selectivity is more detailed than the enzyme specificity, which only describes the amino acids after which an enzyme will cleave a peptide bond. An indication that the pH of hydrolysis influences the enzyme selectivity was found in the tryptic hydrolysis of b-casein (Vorob'ev, Dalgalarrondo, Chobert, & Haertl e, 2000). It was shown that the kinetics of peptide formation and release of peptides with Arg residues were not affected by the changes in pH, while, for peptides after Lys, the pH of hydrolysis did influence the peptide kinetics.…”
Section: Introductionmentioning
confidence: 99%